Effects of home-based exercise with telehealth guidance in lymphoma cancer survivors entering cardio-oncology rehabilitation: rationale and design of the tele@home study - Chamradova, Katerina; Batalik, Ladislav; Winnige, Petr; Dosbaba, Filip; Hartman, Martin; Batalikova, Katerina; Janikova, Andrea; Nehyba, Svatopluk; Felsoci, Marian; Pepera, Garyfallia; Su, Jing Jing (Cardio-oncology (London, England), 2024)
BACKGROUND: Participation in cardio-oncological rehabilitation is low, and the effects incline to decrease after the initial rehabilitation term. Home-based exercise has the potential to enhance involvement in cardio-oncology rehabilitation and was demonstrated to be feasible, safe, and helpful in increasing short-term cardiorespiratory fitness. The lasting effects on cardiorespiratory fitness and physical activity are uncertain. Hence, a novel approach via telehealth management based on objectively measured exercise at home was proposed. OBJECTIVES: To improve self-monitoring, such as self-confidence, behavioral change, and goal setting for individual exercise, and afterward, increase long-term effects concerning cardiorespiratory fitness. DESIGN: This randomized controlled trial compares a 12-week guided home exercise telehealth intervention with a center-based exercise intervention of the same duration and intensity of exercise in lymphoma cancer survivors entering cardio-oncology rehabilitation after treatment. Participants will be instructed to exercise gradually at 60-85% of their maximum heart rate for 30-50 min 3 times a week. Participants will receive individual remote guidance (feedback about frequency, duration, and exercise intensity) by preferred contact (phone call, text message) once a week based on shared exercise data through the web platform. The primary outcome is a change in cardiorespiratory fitness expressed as maximal oxygen uptake assessed through cardiopulmonary exercise test at baseline, 12 weeks, and 1 year. Secondary objectives are quality of life, muscle strength, body composition, incidence of adverse events, and exercise adherence. This study will determine whether a telehealth model is effective and safe compared to a center-based model in cancer survivors and whether exercise prescriptions are followed by participants. Additionally, an overview of the long-term effectiveness of telehealth cardio-oncology rehabilitation will be provided. This approach aligns with the trend of moving non-complex healthcare services into the patients' home environment. TRIAL REGISTRATION: ClinicalTrials.Gov Identifier: NCT05779605.
Keywords: Telehealth; Telemonitoring; Home-based exercise; Cardio-oncology rehabilitation; Cancer survivors